Palladium-Catalyzed Reductive Coupling of Nitroarenes with Phenols leading to N-Cyclohexylanilines - Liu, Kai-Jian; Zeng, Xiu-Ling; Zhang, Yong; Wang, Yi; Xiao, Xin-Sheng; Yue, Huilan; Wang, Ming; Tang, Zilong; He, Wei-Min (Synthesis, 2018)
A direct and efficient palladium-catalyzed reductive coupling reaction of nitroarenes with phenols has been developed. A series of N-cyclohexylaniline derivatives was easily and efficiently obtained in moderate to good yields via C–N bond formation by the simple use of safe and inexpensive sodium formate as the hydrogen donor.
Keywords: green chemistry; palladium catalysis; reductive coupling; nitroarene; phenol; cyclohexylamine